2009
DOI: 10.1002/jsfa.3618
|View full text |Cite
|
Sign up to set email alerts
|

Low humidity after harvest changes the abscission site in bunch cherry tomatoes

Abstract: BACKGROUND: In bunch cherry tomatoes (BCTs) abscission of the fruit from the bunch, rather than deterioration of fruit determines the life-span of the produce. Two abscission sites have been characterised: the joint (AJ) in the middle of the pedicel, and at the receptacle (AR) at the fruit-pedicel interphase. The type of abscission is sensitive to growth conditions; joint abscission is typical of winter harvests whereas receptacle abscission is dominant in summer harvests. The aim of the present study was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…1). Direct effect of the water loss is the reduction in fruit firmness, which is measured by compressing the fruits (Dvir et al, 2009). Jeong et al (2003) were stated a significantly delayed softening by 1-MCP and/or wax while control fruit softened rapidly and completed ripening within 7 day of storage at 20°C.…”
Section: Physical and Chemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Direct effect of the water loss is the reduction in fruit firmness, which is measured by compressing the fruits (Dvir et al, 2009). Jeong et al (2003) were stated a significantly delayed softening by 1-MCP and/or wax while control fruit softened rapidly and completed ripening within 7 day of storage at 20°C.…”
Section: Physical and Chemical Analysesmentioning
confidence: 99%
“…Tomato fruits do not have stomata or lenticels and the fruit is enclosed within a cuticle that forms an effective barrier to water. The rachis is likely to provide a surface for evaporation from itself and from the fruit, which is expected to lead to wilting of the rachis and softening of the fruit (Dvir et al, 2009). So, there is a need to prevent desiccation of stems and sepals that causes to abscission in bunch tomatoes.…”
Section: Introductionmentioning
confidence: 99%
“…8C). Dvir et al (2009) reported that water loss has a direct effect on the appearance of the tomato calyx, which becomes full green in color. In this study, the color change of calyxes was determined by measuring L*, chroma, and hue angle variable.…”
Section: Resultsmentioning
confidence: 99%
“…According to Dvir and Brazilian Archives of Biology and Technology. Vol.63: e20190348, 2020 www.scielo.br/babt coauthors [24], tomato fruits have no stomata or lenticels, being covered by a cuticle that effectively acts in the prevention of dehydration.…”
Section: Discussionmentioning
confidence: 99%